America's trade policy towards Japan : demanding results - Kunkel, John (Routledge advances in international political economy, 2003)
Kunkel combines research in economics, politics and history in this important case study while offering theoretical insights and practical lessons on the forces shaping US trade policy at the start of the twenty-first century.